EXPRESS: Efficacy and tolerability of sequential COP and doxorubicin chemotherapy protocol for treatment of high-grade lymphoma in cats - Kayla Neiderfer; Yoshimi Iwaki; Lindsay L Donnelly; Jennifer E Bryant; Jeffrey N Bryan; Carolyn Henry (Journal of Feline Medicine and Surgery, 2026)
Objectives The aim of this study was to evaluate tolerability of a COP/DOX protocol, where cats received COP (vincristine, cyclophosphamide, and prednisolone) induction weekly for 6 weeks followed by doxorubicin (DOX) consolidation every three weeks for 6 doses. A secondary objective was to evaluate the efficacy of COP/DOX protocol in this cohort of cats. Methods Records were retrospectively reviewed for cats with high-grade lymphoma treated with the COP/DOX protocol from 2005-2024. Data collected included signalment, method of diagnosis, tumor location, staging, baseline diagnostics, drug dosages, adverse events, re-staging diagnostics and treatment response. Progression free survival (PFS) and survival time (ST) were estimated using the Kaplan-Meier method and compared across selected variables using log-rank test. Results Twenty-seven cats met inclusion criteria. The most common form of lymphoma was gastrointestinal in 33.3% of cats. The number of cats achieving a maximal response of clinical remission (CR) and partial remission (PR) throughout COP were 10 (37.0%) and 12 (44.4%), respectively. Of the 5 cats that had stable disease (SD) or progressive disease (PD) during COP, 1 achieved PR on doxorubicin. Four cats (14.8%) did not respond either to the COP or DOX part of the protocol. The overall response rate at 6 weeks after initiation of COP/DOX was 77.7%. PFS was 98 days (Interquartile range (IQR) 41 - 141) and MST was 154 days (IQR 102 – 546). The cats that had CR at the completion of DOX had PFS of 554.5 days and MST of 546 days. High grade adverse events included grade 3 and 4 neutropenia (n=3 for each) during COP. Lymphocyte: monocyte ratio and response at the completion of DOX were significantly associated with PFS and MST. Conclusions and relevance We conclude that the COP/DOX protocol was well tolerated by this population. PFS and MST were similar to previous reports. The COP/DOX protocol is an effective treatment approach for cats with lymphoma.